Does Family Commitment Affect Female Leadership and Productivity? Evidence from a University in Manado - Roosalina Hera Lucia; Steven Yones Kawatak; Bernhard Tewal; Olivia Syanne Nelwan (Journal of Accounting Research, Organization and Economics, 2022)
AbstractObjective – This study has two objectives. Firstly, it is done to determine the influence of female leadership on productivity. Secondly, this study also aims to find out about the impact of family commitment towards the influence of female leadership on productivity at Universitas Katolik De La Salle Manado.Design/methodology – The sample consists of 53 female employees (Lecturers and Staff) at Universitas Katolik De La Salle Manado. This study uses Moderating Regression Analysis to test the hypotheses developed from three different variables, namely female leadership, productivity, and family commitment. Data are analyzed by using Statistical Package for the Social Sciences (SPSS) version 25.Results – The results of this study reveal that female leadership have a positive and significant effect on productivity, however, there is no proves found that family commitment moderates the influence of women's leadership on work productivity at Universitas Katolik De La Salle Manado.